Ab initio study of alkali-metal-based bismuth selenides (A BiSe2; A = K, Na) for photovoltaic and thermoelectric applications - Sanvito, Stefano (My University, 2024)
Iron pentacarbonyl (IPC) gas forms upon the reaction of carbon monoxide with Fe containing metallic surfaces under gas reforming conditions. IPC formation can sometimes reach alarming levels that cause metal loss, pipeline thinning corrosion, catalyst poisoning, and contamination of sensitive industrial equipment. In this work, we demystify using multiscale computational modeling the mechanism of Iron pentacarbonyl formation: Density functional theory (DFT) is used to explore various catalytic reactions that involve a Fe adatom reacting with adsorbed carbon monoxide. Our calculated carbonyls desorption barriers on a perfect and clean Fe surface are too high to allow the carbonyls to form then desorb at temperatures <500 K at the rates reported experimentally. Most importantly, our calculations indicate that a high CO surface coverage, in addition to the presence of Fe adatoms, favors carbonyl formation and its desorption towards the flowing gas medium. Using insights extracted from ab initio molecular dynamics simulations, we propose that the most plausible IPC formation mechanism consists of: (1) on surface reactions of adsorbed CO molecules with an Fe adatom to form iron tricarbonyl (Fe(CO)3*) molecules; (2) an adsorbate assisted movement of iron tricarbonyl on top of the CO adlayer; and (3) the interaction of iron tricarbonyl with CO molecules from the gaseous medium eventually leading to iron adatom removal as Fe(CO)5 gas.
Keywords: Iron pentacarbonyl (IPC); metallic surfaces; Density functional theory (DFT); Iron pentacarbonyl (IPC); metallic surfaces; Density functional theory (DFT)